2021
DOI: 10.1111/jfbc.13806
|View full text |Cite
|
Sign up to set email alerts
|

Combination of cyanidin‐3‐O‐glucoside and cisplatin induces oxidative stress and apoptosis in HeLa cells by reducing activity of endogenous antioxidants, increasing bax/bcl‐2 mRNA expression ratio, and downregulating Nrf2 expression

Abstract: Investigation on potentiation of existing drugs with natural compounds to enhance efficacy and reduce toxic effect of the drugs has been increasing in recent years. This paper reports cytotoxic effect (apoptosis‐related and oxidative stress‐related effect) of cyanidin‐3‐O‐glucoside (C3G), cisplatin (DDP), and their combination (C3G‐DDP) on cervical cancer HeLa cells. Concentration of intracellular reactive oxygen species (ROS) was determined by employing fluorescent marker 2′,7′‐dichlorodihydrofluorescein diac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Balance of Bcl2 family members determines whether a cell undergoes apoptosis or survival (39). Cisplatin increases p53 levels and facilitates the apoptotic response in tumor cells (40); moreover, cisplatin activates Bax, decreases expression of Bcl2 and shifts the Bax/Bcl2 ratio in a pro-apoptotic direction in tumor cells (41). Furthermore, the emergence of p53 mutant cisplatin-resistant OC cells has been demonstrated following drug exposure (42) and patients with OC who have p53 mutations are more resistant to cisplatin-based therapy (43).…”
Section: Discussionmentioning
confidence: 99%
“…Balance of Bcl2 family members determines whether a cell undergoes apoptosis or survival (39). Cisplatin increases p53 levels and facilitates the apoptotic response in tumor cells (40); moreover, cisplatin activates Bax, decreases expression of Bcl2 and shifts the Bax/Bcl2 ratio in a pro-apoptotic direction in tumor cells (41). Furthermore, the emergence of p53 mutant cisplatin-resistant OC cells has been demonstrated following drug exposure (42) and patients with OC who have p53 mutations are more resistant to cisplatin-based therapy (43).…”
Section: Discussionmentioning
confidence: 99%
“…The natural compound cyanidin‐3‐ O ‐glucoside significantly increased Keap1 expression, reducing Nrf2 levels and its target proteins: HO‐1 and NQO1. The latter improves HeLa cells susceptibility to cisplatin treatment 105 . Also, Galanginan, the active principle of galangal, downregulates Nrf2, inducing ROS production and apoptosis in HeLa cells 106 .…”
Section: Targeting Nrf2 In Hpv‐related Cancersmentioning
confidence: 99%
“…The latter improves HeLa cells susceptibility to cisplatin treatment. 105 Also, Galanginan, the active principle of galangal, downregulates Nrf2, inducing ROS production and apoptosis in HeLa cells. 106 Wang et al 80 showed that the inhibition of ATF2 induces Nrf2 depletion and cancer cell sensitivity to BETis, which generates ferroptosis.…”
Section: Targeting Nrf2 In Hpv-related Cancersmentioning
confidence: 99%
“…In particular, this drug combination remarkably increased the expression of PTEN, cytosolic cytochrome c, bax, cleaved caspase-9 and -3 and AIF; moreover, p-AKT and bcl-2 protein expression levels were reduced [ 191 ]. The apoptosis- and oxidative-stress-related effects of cyanidin-3-O-glucoside, cisplatin and their combination were investigated on HeLa cervical cancer cells [ 192 ]. Results showed that cyanidin-3-O-glucoside and cisplatin increased oxidative stress by downregulating Nrf2 and consequently HO-1 and NQO1 expression.…”
Section: Dietary Polyphenols and Drug Synergism In Cancer Therapymentioning
confidence: 99%